Research and application of domestic micro star sensor - Zheng Tuo; Wang Guanya (Dianzi Jishu Yingyong, 2018)
Star sensor is an important part of the attitude control of spacecraft. Based on the homemade anti-radiation CMOS APS chip and SoPC control chip, the optical and electrical system of a miniature star sensor is designed, and finally the miniaturization and localization of star sensor are realized. In order to develop a homemade miniaturized star sensor as the breakthrough point, the key technical issues of its parameter design, system construction and performance are studied. The developed star sensor eventually meets the expected design, and can complete the basic functions.